Determination of erosion and sedimentation potential for sump design at the nickel mine site of PT VALE Petea Indonesia - Badaruddin, Sugiarto (INTEK: Jurnal Penelitian, 2022)
PT. Vale Indonesia plans to mine at the Petea location using the open pit method. If viewed from the watershed boundary, the planned mining location is located in the upstream part of the Lamunto watershed. In connection with the existence of the mining plan, a solution is required to prevent things that can harm and damage the surrounding environment prior to implementation, especially related to soil erosion which is expected to impact the Lamunto watershed which is the outlet of the planned mining location. The method used in this study is to analyse the potential for erosion that occurs using the USLE (Universal Soil Loss Equation) method with the help of the ArcGIS application. Furthermore, the calculation of the sedimentation rate is carried out using the SDR (Sediment Delivery Ratio) equation based on the calculated erosion rate and the area of the mining plan that will be used to plan the sump (sediment storage tank). The results showed that the total sediment potential in sumps A, B, C, D, E, F, G, and H was 550.39 m3/year, 1195.31 m3/year, 1588.43 m3/year, 1908, 27 m3/year, 2423.33 m3/year, 1899.53 m3/year, 1941.76 m3/year, 2169.15 m3/year and 2756.29 m3/year, respectively. From these results it can be seen that the slope factor (LS) is more influential than the catchment area in calculating the sediment potential as evidenced by the total sediment potential in sump D which is greater than sump F.